2021
DOI: 10.1128/jvi.00190-21
|View full text |Cite
|
Sign up to set email alerts
|

Ilaprazole and Other Novel Prazole-Based Compounds That Bind Tsg101 Inhibit Viral Budding of Herpes Simplex Virus 1 and 2 and Human Immunodeficiency Virus from Cells

Abstract: In many enveloped virus families, including HIV and HSV, a crucial, yet unexploited, step in the viral life cycle is releasing particles from the infected cell membranes. This release process is mediated by host ESCRT complex proteins, which are recruited by viral structural proteins and provides the mechanical means for membrane scission and subsequent viral budding. The prazole drug, tenatoprazole, was previously shown to bind to ESCRT complex member Tsg101 and to quantitatively block the release of infectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…For example, it was observed that compounds that block the PPxY–NEDD4 interaction also efficiently inhibited the egress of MARV [ 175 , 176 ]. Similarly, recent studies have shown that prazole compounds can inhibit the release of some enveloped viruses, including HIV-1, EBOV, May aro v irus (MAYV), and HSV by covalently binding the UEV domain of TSG101, which results in the disruption of TSG101–ubiquitin interaction [ 177 , 178 , 179 ]. Such a class of inhibitors interfering with the budding machinery could thus resultingly be extremely useful for impairing the production of newly emerging RNA viruses for which no therapeutics are available.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was observed that compounds that block the PPxY–NEDD4 interaction also efficiently inhibited the egress of MARV [ 175 , 176 ]. Similarly, recent studies have shown that prazole compounds can inhibit the release of some enveloped viruses, including HIV-1, EBOV, May aro v irus (MAYV), and HSV by covalently binding the UEV domain of TSG101, which results in the disruption of TSG101–ubiquitin interaction [ 177 , 178 , 179 ]. Such a class of inhibitors interfering with the budding machinery could thus resultingly be extremely useful for impairing the production of newly emerging RNA viruses for which no therapeutics are available.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this observation, ALIX is required for recruitment of ESCRT-III to the NM during infection of cells with Epstein–Barr virus (EBV, a human gammaherpesvirus) [ 103 , 104 ]. In addition, a compound that binds to ESCRT-I protein TSG101 inhibits primary envelopment of HSV-1 in Vero cells [ 105 ], supporting the idea that ESCRT-III machinery is required for nuclear egress of HSV-1 capsids. The other ESCRT-III adaptor CHMP7 has a predominant role in reformation of the nuclear membrane in various situations [ 101 , 102 ].…”
Section: Primary Envelopmentmentioning
confidence: 91%
“…Prazoles are small molecules that bind the UEV domain near the β-hairpin and disrupt Ub binding there ( [23]; Figure 4). As noted above, they interfere with the ability of HIV-1 Gag to recruit Tsg101 to the plasma membrane assembly site and with the ability of EBV and HSV to mobilize the factors required for immature capsid formation and egress from the nuclear membrane assembly site [25,70]. Through siRNA-mediated depletion/replacement experiments, residue Cys73 in Tsg101 was demonstrated to be the prazole target in the case of HIV-1 and EBV.…”
Section: Small Molecule Inhibition Implicates Non-covalent Ub-binding At the Tsg101 β-Hairpin In Trafficking Of Hiv-1 Ebv And Hsv-1/2 Capmentioning
confidence: 99%
“…The UEV domain is the only region of the protein for which structural information is available at the resolution required for drug design. Most efforts targeting Tsg101 have focused primarily on the PTAP site in that domain and have led to the identification of both cyclic [61][62][63] and multidentate [64][65][66][67] peptide and small molecule inhibitors [24,25,68]. Interestingly, while peptide inhibitors targeting PTAP-dependent Gag budding had no effect on release of a PTAP mutant [61], the small molecule inhibitors targeting UEV Ub-binding inhibit release irrespective of PTAP engagement [23].…”
Section: Small Molecule Inhibition Implicates Non-covalent Ub-binding At the Tsg101 β-Hairpin In Trafficking Of Hiv-1 Ebv And Hsv-1/2 Capmentioning
confidence: 99%
See 1 more Smart Citation